The Current Understanding of Molecular Pathogenesis of Quantitative von Willebrand Disease, Types 1 and 3 - Yadegari, Hamideh; Oldenburg, Johannes (Hämostaseologie, 2020)
Von Willebrand disease (VWD), the most prevalent congenital bleeding disorder, arises from deficiencies in quantity or quality of von Willebrand factor (VWF). The quantitative deficiencies of VWF are considered to be either VWD type 1 (mild/moderate reduction of VWF) or type 3 (virtual absence of VWF). Following cloning of the VWF gene (VWF) in the 1980s, significant progress has been made in our understanding of the pathogenesis of VWD. The genetic basis of type 3 VWD is well defined. VWF causative variations comprising predominantly null alleles have been identified in more than 85% of cases. In contrast, the molecular mechanisms in type 1 disease are only partially characterized. The VWF sequence variations, including mostly missense alterations, are found in only approximately 65% of type 1 VWD patients. It appears that genetic elements outside of VWF may contribute to the pathophysiology of type 1 VWD. This review discusses in detail the current understandings of the genetic basis and molecular mechanisms causing quantitative deficiencies of VWF.
Keywords: von Willebrand factor; von Willebrand disease; bleeding disorder; gene mutation